Analysis of post-transcriptional regulatory signatures and immune cell subsets in premature ovarian insufficiency based on full-length transcriptome - Yu, Zhaoyang; Zhang, Xiqian; Nong, Yingqi; Ding, Hongfan; Fu, Xiaoqian; Li, Feiwen; Liu, Lidan; Li, Mujun; Peng, Weilong; Wu, Huimei; Liu, Fenghua (Scientific reports, 2025)
Premature ovarian insufficiency (POI) is a reproductive endocrine disorder characterized by infertility and the perimenopausal syndrome. Its genetic etiology is highly heterogeneous and not yet fully understood. Limited by short-read sequencing, the profile and structural variation of the full-length transcript for POI have remained elusive. Therefore, this study included peripheral blood samples from 5 POI patients and 5 controls, characterizing full-length transcripts of POI using Oxford Nanopore sequencing firstly. Ultimately, we identified 26,122 transcripts, including 7,724 novel gene loci and 13,593 novel transcripts. A total of 382 differentially expressed transcripts were identified, including 366 down-regulated and 16 up-regulated transcripts. Based on transcript structure variant analysis, 8,834 alternative splicing events, 65,254 alternative polyadenylation sites and 32 motifs were further identified, revealing the diversity sources of transcript isoforms, proteins and genetic complexity. Enrichment analysis of differentially AS genes suggested that the ferroptosis pathway may play an important role in the pathogenesis of POI.Additionally, 494 high-confidence lncRNAs, 1,768 transcription factors, and novel gene-coding regions were predicted based on full-length transcript sequence. Analysis of immune cell subtypes revealed the expression of CD8 + T cells and monocytes were down-regulated in POI, which was significantly positively correlated with AMH, suggesting that CD8 + T cells and monocytes could serve as potential diagnostic markers and immunotherapy targets for POI. Conclusively, this study provides new perspectives on the pathogenesis, post-transcriptional regulation mechanisms, and immune targets of POI.